Outcome of Open Reduction and Internal Fixation of Monteggia Fracture-Dislocation by Small Dynamic Compression Plate (DCP) in Adult Patients (Mugda Medical College Journal, 2025)
Monteggia fractures involve a break in the ulna along with a dislocation of the radial head. Proper and timely anatomical reduction and stable fixation management are critical for successful outcomes. This prospective, observational study was conducted in the National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka, Bangladesh, to assess the effectiveness of open reduction and internal fixation using a small dynamic compression plate (DCP) on the ulna, alongside the anatomical reduction of the radial head in adult patients with early-stage of Monteggia fracture-dislocation, between March 2017 and February 2020. A total of 30 patients with radiologically confirmed closed Monteggia fractures were included through purposive sampling. Outcomes were measured over 24 weeks following operation using the Quick DASH (shortened disabilities of the arm, shoulder, and hand questionnaire) score, visual analogue scale (VAS), and range of motion (ROM) for flexionextension and supination-pronation and evaluated against Anderson criteria for functional outcomes. The average age of the patients was 36 years; a male predominance was observed (80%). The majority had Bado type I fractures (86.7%), with the remainder having type II. The average time from injury to surgery was approximately 10 days. Post-operative complications occurred in 13.3% of cases, including tourniquet palsy and wound infections. Functional outcomes rated 23.3% as excellent, 63.3% as good, 6.7% as fair, and 6.7% as poor. Overall, 86.7% of outcomes were satisfactory. Patients with Bado type II fractures and those with longer intervals between injury and surgery experienced worse outcomes (p=0.004 and p=0.012, respectively). Open reduction and internal fixation approach for Monteggia fractures leads to predominantly excellent to good outcomes. Factors such as fracture type and delay in surgical intervention significantly impact recovery, highlighting the importance of prompt treatment. Despite resource limitations, early surgical intervention is recommended to prevent complications and enhance recovery.Mugda Med Coll J. 2025; 8(1): 17-22